Dental Education in the Time of COVID-19 Pandemic: Challenges and Recommendations - Hassan, Mohamed G.; Amer, Hala (Frontiers in Medicine, 2021)
Moving within the second wave of the coronavirus (COVID-19) pandemic, dental education delivery has been profoundly affected by this crisis, so has the structure, evaluation and future of dental education. Both pre-clinical and clinical dental education have seen challenges ranging from fully online educational content to limited dental training for senior dental students. This crisis appears to be a tipping point that produced confusion in dental teaching especially clinical sciences. Although medical institutions immediately started to adapt to the COVID-19 pandemic, dental and oral health educational services are deeply affected due to the dental team's proximity to the patient and the aerosols through routine dental therapeutic procedures. Dental students unlike other medical students are considered to be at the highest risk due to the nature of their clinical training that includes working in the oral cavity of patients using aerosol-generating equipment. Some institutions have taken the initiative and documented their modifications during the pandemic; however, there is a serious need for further analysis and wide range screening of the situation in the dental schools during the COVID-19 crisis. The aim of this mini-review is to present these challenges and how academic and clinical educators in academic dental institutions have worked to overcome them.